IMPLEMENTASI PRINSIP MENGENAL NASABAH (KNOW YOUR CUSTOMER) SERTA PENGARUHNYA TERHADAP TINDAK PENCUCIAN UANG (MONEY LAUNDERING) DAN KINERJA KEUANGAN PADA LEMBAGA PERBANKAN - Julyana Wijaya (Universitas Bunda Mulia, 2017)
The purpose of this paper is to examine the effect of the implementation of Know Your Customer to the banks financial performance. Quantitaive description analysis was used to evaluate the answers of 26 respondents from a questionnaire. Descriptive statistic shows that 60%-70% respondents agreed that there is an effect from the implementation of KYC against money laundering action and financial performance of financial institution.However regression analysis shows that there is no significant effect between implementation of KYC and financial performance of financial institution. Keywords: Money Laundering, Know Your Customer, Fiancial Performance